Extra‐powerful on the visuo‐perceptual space, but variable on the number space: Different effects of optokinetic stimulation in neglect patients. Issue 2 (22nd August 2014) - Pitteri, Marco; Kerkhoff, Georg; Keller, Ingo; Meneghello, Francesca; Priftis, Konstantinos
Abstract : We studied the effects of optokinetic stimulation (OKS; leftward, rightward, control) on the visuo‐perceptual and number space, in the same sample, during line bisection and mental number interval bisection tasks. To this end, we tested six patients with right‐hemisphere damage and neglect, six patients with right‐hemisphere damage but without neglect, and six neurologically healthy participants. In patients with neglect, we found a strong effect of leftward OKS on line bisection, but not on mental number interval bisection. We suggest that OKS influences the number space only under specific conditions.